2020
DOI: 10.15408/etk.v19i2.15528
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Macro-risk Indicators, Internal Factors, and Risk Profile of Islamic Banking in Indonesia

Abstract: This study is essential because of Islamic  banks have a level of health with higher NPF than conventional banks and purposes to examines whether macroeconomic indicators (macro-risk), internal factors of banking (GCG-earnings-capital ) and risk profile have correlation in term Indonesian Islamic banking. The method used is the correlation analysis involving four macro-risk variables (Forex; BI rate; Inflation and GDP), three GEC variables (GCG; ROA, and CAR) and two risk profile (FDR and NPF). The number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The high economic growth proved that the welfare of the people was improving, leading to the actualization of consumption, and debt repayment obligations. These results were in line with Badar and Javid ( 2013 Munifatussaidah (2020); Nugrohowati and Bimo (2019); also Santosa et al (2020), GDP positively and significantly impacted NPF. Meanwhile, the study conducted by (Asmara, 2019;Prastowo & Usman, 2021;Yuniarti et al, 2022) found that GDP was ineffective on NPFs.…”
Section: Resultssupporting
confidence: 82%
“…The high economic growth proved that the welfare of the people was improving, leading to the actualization of consumption, and debt repayment obligations. These results were in line with Badar and Javid ( 2013 Munifatussaidah (2020); Nugrohowati and Bimo (2019); also Santosa et al (2020), GDP positively and significantly impacted NPF. Meanwhile, the study conducted by (Asmara, 2019;Prastowo & Usman, 2021;Yuniarti et al, 2022) found that GDP was ineffective on NPFs.…”
Section: Resultssupporting
confidence: 82%
“…The effect of the correlation between macroeconomic variables and internal variables (NPF) refers to the theory explained by (Miskin, FS, 2011) regarding the correlation between macroeconomic variables, finance, and banking stability. This influence begins with the emergence of shock changes in macroeconomic variables (inflation, GDP, exchange rates) (Santosa et al, 2020).…”
Section: Non-performing Financingmentioning
confidence: 99%
“…Research by stated that Islamic banks are more efficient due to economic conditions and political stability. Research by (Filip, 2017;Santosa et al, 2020) shows that GDP negatively affects NPF. However, it differs from research by (Kusmayadi et al, 2017), which stated that GDP positively affects NPF.…”
Section: The Effect Of Gdp On Non-performing Financingmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it considers previous studies in which banking stability was only discussed at the institutional level. Some, such as that of Santosa et al (2020), explain that Islamic bank stability is affected by macroeconomic conditions. In addition, comparing conventional and Islamic bank stability, Olson & Zoubi (2017), Trad et al (2017), Asutay & Othman (2020), Hassan et al (2019), Safiullah (2021), Bilgin et al, (2021) and Louhichi et al, (2019) conclude that Islamic banks are superior in terms of banking stability during financial turmoil and in tight banking competition.…”
Section: Introductionmentioning
confidence: 99%